2019
DOI: 10.1080/00223891.2019.1639188
|View full text |Cite
|
Sign up to set email alerts
|

An Inventory of Problems–29 Study on Random Responding Using Experimental Feigners, Honest Controls, and Computer-Generated Data

Abstract: Self-reports may be affected by two primary sources of distortion, i.e., content-related (CRD) and content-unrelated (CUD) distortions. CRD and CUD, however, may co-vary, and similar detection strategies have been used to capture both. Thus, we hypothesized that a scale developed to detect random responding-arguably, one the most evident examples of CUDwould likely be sensitive to both CUD and, albeit to a lesser extent, CRD. Study 1 (N = 1,901) empirically tested this hypothesis by developing a random respond… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…A comparison with TOMM based on 100 adult volunteers showed excellent values for sensitivity and specificity, but even higher values were obtained by combining the two measures (Giromini, Barbosa, et al, 2019). The IoP-29 has proven its usefulness in separating honest from random responders (Giromini et al, 2020a(Giromini et al, , 2020bWinters et al, 2021), and honest responders from those simulating depression, PTSD, and/or schizophrenia (Giromini et al, 2020a(Giromini et al, , 2020bPignolo et al, 2021;Šömen et al, 2021). A study of 154 possibly traumatized firefighters showed that IoP-29 FDS scores based on honest responding were almost consistently below cutoff, despite high variation in symptom presentation (Carvalho et al, 2021).…”
mentioning
confidence: 99%
“…A comparison with TOMM based on 100 adult volunteers showed excellent values for sensitivity and specificity, but even higher values were obtained by combining the two measures (Giromini, Barbosa, et al, 2019). The IoP-29 has proven its usefulness in separating honest from random responders (Giromini et al, 2020a(Giromini et al, , 2020bWinters et al, 2021), and honest responders from those simulating depression, PTSD, and/or schizophrenia (Giromini et al, 2020a(Giromini et al, , 2020bPignolo et al, 2021;Šömen et al, 2021). A study of 154 possibly traumatized firefighters showed that IoP-29 FDS scores based on honest responding were almost consistently below cutoff, despite high variation in symptom presentation (Carvalho et al, 2021).…”
mentioning
confidence: 99%
“… Specifically computed to convert traditional scores into a binomial experiment; 1–3, Acquisition trials; Animals, Category fluency (Curtis et al., 2008; Hurtubise et al., 2020; Sugarman & Axelrod, 2015); BC, Below chance level (below the 95% confidence interval around the mean); BIN, Cutoff based on the binomial distribution; BNT‐15, Boston Naming Test—Short Form (Abeare et al., 2022; Deloria et al., 2021; Erdodi, Dunn, et al., 2018); C, At chance level (within the 95% confidence interval around the mean); CD WAIS‐IV , Coding (Ashendorf et al., 2017; Erdodi, Abeare, et al., 2017); CIM, Complex Ideational Material (Erdodi, 2019; Erdodi et al., 2016; Erdodi & Roth, 2017); COL, Color Naming; CPT‐3, Conners' Continuous Performance Test—Third Edition ( T = 90 is the highest score possible; Ord et al., 2020; Robinson et al., 2022); COM, Combination score (FR + true positives—false positives); DCT, Dot Counting Test (Boone et al., 2002; Hansen et al., 2022); Dem ADJ , Demographically adjusted score; DH, Dominant hand; D‐KEFS, Delis Kaplan Executive System (Cutler et al., 2022; Eglit et al., 2020; Erdodi, Sagar, et al., 2018); DR, Delayed recall; DS WAIS‐IV , Digit Span subtest of the Wechsler Adult Intelligence Scale—Fourth Edition (Shura et al., 2020; Whitney et al., 2009); EMP, Empirically derived cutoffs; EWFT, Emotion Word Fluency Test (Abeare, Hurtubise, et al., 2021); FAS, Letter fluency (Curtis et al., 2008; Deloria et al., 2021; Hurtubise et al., 2020); FCR, Forced choice recognition; FR, Free recall; FTT, Finger Tapping Test (Arnold et al., 2005; Axelrod et al., 2014; Erdodi, Taylor, et al., 2019); GPB, Grooved Pegboard Test (Erdodi, Kirsch, et al., 2018; Erdodi, Seke, et al., 2017; Link et al., 2021); HVLT‐R, Hopkins Verbal Learning Test—Revised (Cutler et al., 2021; Sawyer et al., 2017); IOP‐M, Inventory of Problems—29 memory module (Giromini et al., 2020a, 2020b; Holcomb, Pyne, et al., 2022); IR, DR & CNS, Immediate, Delayed & Consistency of Recognition trials (% correct); LM Recognition, Yes/No recognition trial of the Logical Memory subtest of the Wechsler Memory Scale—Fourth Edition (Bortnik et al., 2010; Dunn et al., 2021); LNS WAIS‐IV , Letter‐Number Sequencing (Erdodi &amp...…”
Section: Discussionmentioning
confidence: 99%
“…Thus, one might question whether our findings generalize to reallife evaluation contexts which use these precautions. On the other hand, inattentive item review or inconsistent effort would likely obscure discrimination of feigners from honest responders (Giromini et al, 2020c). Indeed, we had no control over the participants, so feigners might have searched the internet for the answers or asked family members and friends how to respond to the items, etc.…”
Section: Overall Discussionmentioning
confidence: 99%